2022
DOI: 10.1177/0148558x221091803
|View full text |Cite
|
Sign up to set email alerts
|

Free Cash Flows and Price Momentum

Abstract: This study investigates the role of free cash flows and (cross-sectional and time-series) price momentum in predicting future stock returns. Past returns and free cash flows each positively predict future stock returns after controlling for the other, suggesting that cash flows and momentum both contain valuable and distinctive information about future stock returns. A strategy of buying past winners with high free cash flows and shorting past losers with low free cash flows significantly outperforms the tradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 75 publications
1
4
0
1
Order By: Relevance
“…However, if companies employ net cash flows for other purposes, for example, investing in property, plant, and equipment, joining other business ventures, paying dividends, they may not have business continuity. This informative value of FCF is in line with previous studies, for instance Sapuan et al (2021), Fu et al (2022, Aburisheh et al (2022), and Tee (2023). The implication of this finding is important.…”
Section: The Informative Value Of Free Cash Flow On Corporate Sustain...supporting
confidence: 91%
See 1 more Smart Citation
“…However, if companies employ net cash flows for other purposes, for example, investing in property, plant, and equipment, joining other business ventures, paying dividends, they may not have business continuity. This informative value of FCF is in line with previous studies, for instance Sapuan et al (2021), Fu et al (2022, Aburisheh et al (2022), and Tee (2023). The implication of this finding is important.…”
Section: The Informative Value Of Free Cash Flow On Corporate Sustain...supporting
confidence: 91%
“…The findings highlighted a positive and significant effect of FCF on firm performance. Fu et al (2022) stated that cash flows contained informative value of future stock returns. The study recommended that buying when high FCF and selling with low FCF significantly affects the traditional trading strategy.…”
Section: Free Cash Flow Conceptmentioning
confidence: 99%
“…We found a study (Guermazi & Bouri, 2017) that used free cash flow as a moderating variable and the resulting free cash flow moderated debt and managerial entrenchment. Fu et al (2022) explained that previous returns and today's free cash flows could lead to forecasting stock returns. However, the research concluded that they might be under-recognised to notice unexplainable risk factors for their findings due to undone risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Free cash flow highlights financial health for firms to decide on new strategies for the future period. Fu et al (2022) research pointed out that cash flows are recognizable from accruals in forecasting future returns. For investors, free cash flow shows consistency in producing cash so that investors feel secure to invest.…”
Section: Introductionmentioning
confidence: 99%
“…‫قهمأل‬ ‫هلهدمضهاألد‬ ‫ألر‬ ‫هلاتثمسق‬ (Houcine, 2013;Tang et al, 2014;Duarte et al, 2022 (Jones, 1991;Dechow et al, 1995;Kasznik, 1999). (Gan, 2006;Yu and Jiang, 2010;Teng and Liu, 2018;Fu et…”
mentioning
confidence: 99%